Encouraging people to set lower personal carbon budgets: anchoring is more effective than social reference groups - Flecke, Sarah Lynn; Aparicio, Erika; Malthouse, Eugene (Frontiers in Psychology, 2025)
Enabling people to set personal carbon budgets may help them to track and reduce their carbon footprint over time. In this study, we investigated ways to encourage a representative sample of the UK population (N = 2,047) to reduce their carbon footprint by setting themselves a lower carbon budget. In an online experiment, we simulated a carbon footprint calculator based on personal spending and tested the effects of two carbon footprint anchors (low vs. high) and three social reference groups (people in the UK vs. customers at the same bank vs. people with similar expenditure) on the carbon budget set by participants. We found that providing a low anchor, independent of the corresponding social reference group, was significantly associated with setting a lower carbon budget. Setting a lower carbon budget was associated with greater motivation and self-reported willingness to change behaviour to adhere to the budget.